Mapping the Evolution of Institutional Governance in Disaster Risk Reduction: A Bibliometric Analysis - Aduma Lestariastuty Situmorang; Sri Setiawati Tumuyu; Bagus Aryo (JAMBURA GEO EDUCATION JOURNAL, 2026)
Institutionalization, understood as the spatially embedded process of translating ideas into formalized programs, governance arrangements and practices, that critical in strengthening community resilience, particularly within the context of Disaster Risk Reduction (DRR). Despite growing global research in DRR, the geographic dimensions of community institutionalization and its influence in local-level disaster governance remained underexplored. This study adopted a geographic perspective to examine global patterns and regional disparities in research in DRR institutionalizational governance. A systematic review combined with Bibliometric Analysis (BA) was conducted to map the global research lanscape. Using VOSviewer, 41 peer-reviewed journal articles indexed in Scopus were analyzed to identify key trends, thematic clusters, and geographic concentrations of scholarship. The findings revealed that while scholarly interest spans multiple continents, research output was disproportionately concentrated in high-income or more developed countries. Regions with high disaster exposure, particularly Asia and Africa remain underrepresented in international peer-reviewed literature. This imbalance does not reflect an absence of DRR practices in these regions; rather, it stems from structural, historical, and institutional differences affecting research production, publication and visibility. Many Asian and African DRR initiatives are robust in practices but often documented in grey literature, government reports, or local-language publications rather than peer-reviewed journals. As a result, critical dimensions of community institutionalization such as local governance structures, decision-making processes, and institutional sustainability remain underexamined, due to the dominance of technical and engineering-focused research. The complexity of community institutions, limited social-science funding, and political sensitivities further constrain scholarly attention. This study highlighted the need for inclusive, context-sensitive and geographically grounded research approaches alongside sustained investment in local research capacity for enhancing DRR effectiveness and sustainable adaptive resilience.